APHORISMS, HORIZONS, AND THE LIMITS OF INTERPRETATION: FROM NIETZSCHE TO HIPPOCRATES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In his reflections on philology, Nietzsche explicitly situates himself within the tradition of Schleiermacher and Boeckh. For Nietzsche, philology is first and foremost “that venerable art which demands of its votaries one thing above all: to go aside, to take time, to become still, to become slow—it is a goldsmith’s art and connoisseurship of the word which has nothing but delicate, cautious work to do and achieves nothing if it does not achieve it lento” (Daybreak, preface). Philology thus emerges not simply as a methodological discipline, but as an ethos—a way of approaching language with slowness, precision, and interpretive care.